¡Muy pop! : conversations on Latino popular culture - Stavans, Ilan; Aldama, Frederick Luis; Michigan Publishing (University of Michigan) (The University of Michigan Press, 2013)
A book-length conversation between two leading scholars on the themes and questions of Hispanic popular culture
Keywords: Stavans, Ilan : Interviews; Aldama, Frederick Luis, : 1969- : Interviews; American literature : Hispanic American authors : History and criticism; Hispanic American arts; Hispanic Americans and mass media; Hispanic Americans : Intellectual life; Popular culture : United States; Hispanic Americans : Social life and customs